Manajemen Pengembangan Pendidikan Tinggi Islam Berwawasan Transformatif Hidayatullah Kota Batam - Maisah, Maisah; Siregar, Isropil; MY, Mahmud; Munte, Rita Sahara (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
Islamic higher education faces significant challenges in adapting to the demands of globalization, technological advancements, and sociopolitical changes. These challenges highlight the need for transformative management approaches that align institutional goals with the development of graduates who embody strong Islamic character and global competencies. Previous studies have identified gaps in integrating Islamic values across all aspects of governance and education, including curricula, organizational culture, and professional ethics. This study aims to address these gaps by exploring transformative management practices in private Islamic universities in Batam, Indonesia. Employing a qualitative research approach with a phenomenological perspective, the study gathered data through in-depth interviews, participatory observations, and document analysis. The findings reveal that transformative management requires not only curriculum innovation and the integration of Islamic principles but also sustained training for educators and effective use of technology to enhance teaching quality and institutional competitiveness. Despite these efforts, challenges such as limited human resources, insufficient funding, and resistance to change hinder full implementation. The study underscores the importance of cross-sector collaborations involving governments, educational institutions, and Islamic organizations to overcome resource constraints and foster innovative practices. The implications are profound, offering a framework for creating educational environments that balance academic excellence with the moral and spiritual growth of students. In conclusion, this research contributes to the development of management strategies for Islamic higher education that are holistic and inclusive, laying the groundwork for institutions to serve as agents of transformation within society while maintaining their Islamic ethos.